Synthesis and biocidal screening of Bromo-Substituted 4-biphenyl acetamides derivatives. - Agarwal, Dr. Jitendra Mohan (International Journal of Scientific Research and Management (IJSRM), 2017)
The present paper deals with the synthesis of Bromo-Substituted 4-biphenyl acetic acid amides by condensation of corresponding acid chlorides with suitable amines. the structure of newly synthesized compounds were elucidated on the basis of their IR, TLC and elemental analysis data. The compounds were also screened for their anti-bacterial and anti-fungal activity.